Strategi Peningkatan Manajemen Kurikulum dalam Pengembangan Mutu SDM Menuju Terwujudnya Lulusan Madrasah Aliyah Berwawasan Internasional - Djuwarijah, Djuwarijah (el-Tarbawi, 2013)
<!--[if gte mso 9]> <![endif]--> The urgent orientation of curriculum management on the context ofdeveloping human resources quality especially about out put of educationat internasional Islamic senior high school is a effort to achieve four(4) primary competences; academic competence, personal competence,social competence, and spiritual competence. For improving curriculummanagement in order to develope human resource quality, InternationalIslamic high school has to apply good strategy to reach competitif andqualified its educational out put. Its strategies are: first, strategy basedon organization system approach where it stresses to organize curriculumindependently, creatively, and innovatively by the Islamic sinior high school. Second, strategy based on purposes focus approach covering several aspects; inquiring sciences, inquiring standart skill standart, inquiring coompetence, character building, and mastering ability for solving social problem of children. Third, strategy based on competence approach focusing on inquiring certain competence based on the development stapes of children. The success of strategies also should be supported by school leader’s ability to mobilize resources potentiality that available at school. <!--[if gte mso 9]> Normal 0 false false false IN X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->